2016
DOI: 10.3389/fncel.2016.00165
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Exercise Induces Astrocytic Structural Plasticity in the Globus Pallidus

Abstract: Changes in astrocyte morphology are primarily attributed to the fine processes where intimate connections with neurons form the tripartite synapse and participate in neurotransmission. Recent evidence has shown that neurotransmission induces dynamic synaptic remodeling, suggesting that astrocytic fine processes may adapt their morphologies to the activity in their environment. To illustrate such a neuron-glia relationship in morphological detail, we employed a double transgenic Olig2CreER/WT; ROSA26-GAP43-EGFP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…We here tested whether some non-neuronal markers colocalized with Olig2, but we did not identify any one with this feature: astrocytes by use of ALDH1L-1, and neurons with NeuN (Figures 5A,D ). Although there is emerging evidence of an Olig2-lineage of astrocytes (GFAP-negative) ( Tatsumi et al, 2016 , 2018 ), to date there is no robust quantitative analysis of this population. Furthermore, Olig2 did not co-label with basal lamina and endothelial cells markers such as Isolectin B4 and Collagen IV basement membrane.…”
Section: Discussionmentioning
confidence: 99%
“…We here tested whether some non-neuronal markers colocalized with Olig2, but we did not identify any one with this feature: astrocytes by use of ALDH1L-1, and neurons with NeuN (Figures 5A,D ). Although there is emerging evidence of an Olig2-lineage of astrocytes (GFAP-negative) ( Tatsumi et al, 2016 , 2018 ), to date there is no robust quantitative analysis of this population. Furthermore, Olig2 did not co-label with basal lamina and endothelial cells markers such as Isolectin B4 and Collagen IV basement membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors can contribute to the deficit of GABA uptake by GAT-3, such as maladaptive structural plasticity or the alteration of GAT-3 trafficking to astrocyte plasma membranes. Structural plasticity has been observed in GP astrocytes during running activity (Tatsumi et al, 2016), which suggests that they actively contribute to motor functions. We recently showed that astrocytosis takes place in the GP in response to chronic dopamine loss (Charron et al, 2014), which suggests that maladaptive structural plasticity of the tri-partite synapse, such as astrocyte processes retraction, could also contribute to GAT-3 deficiency by removing the transporters from GABAergic terminals.…”
Section: Astrocytic Gat-3 Dysfunction Is Responsible For Tonic Inhibimentioning
confidence: 99%
“…Recently, we found that Olig2-lineage astrocytes clustered in specific brain nuclei in the adult mouse (Tatsumi et al, 2016 ). During lineage-tracing studies of cells expressing Olig2 in Olig2 CreER ; ROSA-GAP43-EGFP mice (Tatsumi et al, 2008 ), we found that Olig2-lineage mature astrocytes preferentially cluster in the globus pallidus, which exerts pivotal functions in the indirect pathway of the basal ganglionic circuit.…”
Section: Introductionmentioning
confidence: 96%
“…In the adult brain, most Olig2 cells co-express NG2 proteoglycan and are termed adult oligodendrocyte progenitor cells (OPCs) (Goldman, 2003 ). They generate mainly OPCs/NG2 glia or mature oligodendrocytes and a subset of astrocytes, but not neurons (Dimou et al, 2008 ; Tatsumi et al, 2016 ). In injured or pathological states of the adult brain, Olig2 cells generate OPCs/NG2 glia, mature oligodendrocytes and a portion of reactive astrocytes, but, again, not neurons (Magnus et al, 2008 ; Tatsumi et al, 2008 ; Islam et al, 2009 ; Zhao et al, 2009 ; Guo et al, 2011 ; Shimizu et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%